Energy system and economy-wide implications of a rapid transition to decarbonized energy in South Africa - Tara Caetano; Bruno Merven (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Developed as well as developing countries will have to increase their ambition relative to their stated Nationally Determined Contributions to limit global temperature increases to 2êC above pre-industrial levels. South Africa's Nationally Determined Contribution, in line with national policy, is to follow a peak, plateau, and decline emissions trajectory to 2050, with the contribution post-2030 contingent on a fair contribution from other countries. Given the high levels of unemployment, poverty, and inequality in South Africa, there are concerns that a rapid transition to a low-carbon energy system would have severe socioeconomic consequences. This paper builds on initial work from the Deep Decarbonisation Pathways Project, and analyses the impacts on the energy system and the economy of an increase in ambition, in order to shed light on these concerns. The key policy recommendation from this analysis is that further investments in fossil fuel infrastructure in South Africa will have significant negative socioeconomic implications, and that further work should be done to reassess development pathways that could mitigate these negative impacts.
Keywords: Q43; Q54; I3; E13; 330; energy; climate policy; welfare; economy-wide model; South Africa